This land of ours –protecting ownership, interest and dealings in land - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah; Ali, Zuraidah (IIUM Press, 2023)
This article highlightsthe contribution of AlmarhumTan Sri Harun M. Hashim in laws relating to land and trusts.The research methodology employed for this study is legal doctrinal, throughanalysing Tan Sri’sjudicialdecisionson land law and the law of trusts. This study reveals that Almarhum TanSri Harun M. Hashimhad contributed to a vast spectrum of knowledge revolvingaroundland and trusts which is in line with Islam, culture,and values. Tan Sri had addressed and contributed tothedevelopment of legal principles in landlawincluding charge, caveat, prohibitory orders, as well as equityand trust principles.Careful consideration of the findings of the review disclosesthe personal attachment and devotion of the work of Almarhum Tan Sri Harun M. Hashim to the legal development inupholding justiceuniversally as well as tothe litigants. As such, the late Tan Sri did not confine his career only asa judge but was also actively involved inand servedas a committee member in justice related organisations. The end ofhiscareer as a judge saw him continue as an academic, providing a widerplatform for him to propagate justice in the preparation of future lawyers and judges.